Making European Muslims: Religious Socialization Among Young Muslims in Scandinavia and Western Europe - Sedgwick, Mark (Routledge Studies in Religion, 2014)
Making European Muslims provides an in-depth examination of what it means to be a young Muslim in Europe today, where the assumptions, values and behavior of the family and those of the majority society do not always coincide. Focusing on the religious socialization of Muslim children at home, in semi-private Islamic spaces such as mosques and Quran schools, and in public schools, the original contributions to this volume focus largely on countries in northern Europe, with a special emphasis on the Nordic region, primarily Denmark. Case studies demonstrate the ways that family life, public edu